Optimization of Lemongrass Oil (Cymbopogon citratus) Emulsion with the Addition of Cethyl Alcohol as a Natural Cosurfactant - Pradasari, Aprilina Siska; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2023)
Lemongrass oil (Cymbopogon citratus) is a plant that produces essential oils as a raw material for fragrance in cosmetics and perfumes. This study aims to determine the optimum conditions for the preparation of Lemongrass oil-wall emulsion (Tween 80 and Cethyl Alcohol) and to determine the effect of the independent variable in the form of the ratio of lemongrass oil-wall to the viscosity produced using the Response Surface Methodology (RSM). The novelty in this research is lemongrass oil with the addition of Tween 80 and Cethyl Alcohol as natural cosurfactants. Tests were carried out with three independent variables, namely stirring time (15, 20 and 25 minutes), stirring speed (20,000, 22,000 and 24,000 rpm) and lemongrass oil-wall ratio (1:3, 1:4, 1:5), which will be designed with the RSM method to obtain optimum operating conditions. Based on the results obtained, the optimal formula for lemongrass oil emulsion is on the 14th running result, which has a pH value of 6.4; density of 0.852; viscosity of 15,450 cP, type M/A, homogeneous and good stability without any change in colour, aroma, and texture. The influence of the lemongrass oil-wall ratio variable, namely the ratio variable, obtained a P-value of 0.000005, which means it is smaller than the value of α = 0.05 so that it can be said that the ratio has a significant effect on the viscosity of the emulsion.